Risorse educative aperte e sperimentazione didattica Le proposte del progetto Innovascuola-AMELIS per la condivisione di risorse e lo sviluppo professionale dei docenti - Ranieri, Maria (Strumenti per la didattica e la ricerca, 2012)
The book proposes an open and collaborative approach to the production of digital teaching contents and to teachers' professional development. Starting from an initial excursus on the undertakings of the Open Educational Resources movement and on the value of collaboration in and among schools, it deals with the topic of teacher training as a back-up to innovation processes, with particular reference to multimedia whiteboards. The theoretical reflection is integrated with the results of the AMELIS biennial project, carried out alongside a network of schools within the Innovascuola (2008-10) framework, and with a presentation of the digital teaching resources produced by the network. Completing the volume, these resources are also available on-line in the form of files and multimedia materials. Conveying the wealth of the experience, they offer teachers and educators useful resources for their teaching activities.